Strategi Kepemimpinan Pondok dalam Menerapkan Akhlak Santri di Pondok Pesantren Miftahul Arifin Bantaran Kabupaten Probolinggo - Febi Fatlika Nurussofiah; Devy Habibi Muhammad; Benny Prasetiya (ISLAMIKA, 2023)
Islamic education plays an important role in the process of forming one's character in order to have a person who has good morals, when the input received is good it will produce something good and vice versa. Because education as the formation of children's character must be given proper attention, therefore educational institutions such as Islamic boarding schools are commonly referred to as a solution for parents and society to shape children's character into individuals who have good morals. So the purpose of this research is to find out how the strategy for implementing morals is by the leader of the Miftahul Arifin Islamic Boarding School in Bantaran, Probolinggo Regency. This research is a qualitative research using a descriptive approach with data collection methods from observations, interviews, and documentation. From the results of the study, that the leadership of the Miftahul Arifin Islamic Boarding School in applying the morals of the students brought very significant changes to the students in educating children to become individuals who have good morals. Therefore the researchers concluded that the strategy that the leader gave had a very important and influential impact on the students at the Miftahul Arifin Islamic Boarding School in Bantaran, Probolinggo Regency.